Only Western influence? The birth of literary Romantic aesthetics in Bengal - Ivbulis, Viktors (Acta Orientalia Vilnensia, 2008)
University of Latvia Much has been said about how fruitfully European aesthetics worked on the minds of Indian writers in the 19th century. For this reason Rabindranath Tagore (1861–1941), even before he turned twenty, in the eyes of some of his compatriots was already a Romanticist—‘the Shelley of Bengal’. Of course, he could not be Shelley because of the very different historical circumstances of India and England (in India at that time historically could not be born aesthetic rebels like Shelley). But what was implied in this assertion remains: in Bengali writing about Tagore and his embarkation upon new aesthetic approaches, almost always the view is expressed that this happened only because of foreign influences. The task of this paper is to show very summarily that such a conclusion may not be correct.